PLANNING AND CONDUCTING INTERNAL AUDIT IN PRACTICE IN THE PRIVATE SECTOR - Jović, Zorica (Poslovna ekonomija, 2021)
During the data collection process to understand and assess risk, internal auditors gain significant insight into operations and opportunities for improvement that can be extremely beneficial to the organization. This paper presents valuable insights into practical work that will assist internal auditors in the process of planning and conducting internal audit in the private sector. In the process of internal audit, it primarily starts from planning through the creation of an audit universe that includes a list of all potential audits based on risk and exposure assessment. The chief audit executive develops an annual action plan based on the audit universe. The annual plan should be broken down into four quarters and each defined audit should be arbitrarily assigned to one quarter. The beginning of the process of the planned audit begins with preparatory activities that include defining the objectives of the individual audit, preparation of a detailed schedule of the individual audit, conducting a preliminary survey. Then, audit sampling techniques (defined as the application of audit procedures to less than 100% of items within a class of transactions or account balance so that each sample unit has a chance to be selected) perform sample selection from the population. According to the selected model, the audit is approached on the basis of which the opinion of the internal auditor is issued in the created engagement report.